Shingles: a harbinger of chronic HIV infection. Issue 6 (2nd November 2021) - Zachariah, S.; Sullivan, A.; Donato, A.
ABSTRACT: Early diagnosis and treatment are essential to reduce the risk of community transmission and morbidity and mortality of individuals infected with HIV. A 49-year-old woman presented with a painful, vesicular rash on the left side of her neck after being treated with valacyclovir for a separate perianal rash. She admitted recent weight loss and diffuse lymphadenopathy. She reported one family member with HIV but denied intravenous drug use or recently new sexual partners. Serum HIV-1 antibody screen was positive. Herpes zoster reactivation is associated with waning immunity in chronic HIV and should prompt testing. Delays in treatment impacts short-term and long-term prognosis for patients infected with HIV.